Lecturer’s Attitudes on Lesson Planning and Their Impact on Pedagogical Practices - Nurul Puspita; Rudi Hartono; Yuliati (Universitas Islam Negeri Palopo, 2026)
Lesson planning is an important professional responsibility in higher education; however, the connection between lecturers’ personal attitudes toward planning and their real pedagogical practice has yet to be explored. Unlike school teachers, university lecturers have great autonomy to design their own course plan and assess their research output rather than their teaching performance. This research aims to investigate the influence of lecturers’ attitudes towards lesson planning on their pedagogical practice within a higher education context. The researcher employed a qualitative research design. The data were collected through semi-structured interviews and document analysis with eight lecturers in the English Education Study Program, UIN Raden Intan Lampung. After the data were collected, the researcher analyzed them thematically and identified three significant categories. First, the lecturers view lesson planning as an administrative and pedagogical instrument, demonstrating a positive attitude. Second, these attitudes strongly influence pedagogical practice by filtering, framing, and guiding it. In this context, beliefs reveal the particular ways, tasks, and assessments that lecturers integrate into their lesson planning. Third, when gaps occur between lecturers’ attitudes and their pedagogical practice, the fundamental causes are typically structural, such as time limitations, large class size, and inadequate resources. The research suggests that lecturers' attitudes towards lesson planning serve as the operational mechanism, evaluative standard, and motivational foundation for pedagogical practices in higher education. It is recommended that institutions promote the expansion of positive professional beliefs and identify organizational conditions that support these beliefs so they can be fully understood in teaching.